INTEGRATION OF 2D SECURE BARCODE IN IDENTITY CARDS: WITH ADDITIONAL SECURITY FEATURES (International Journal of Engineering and Computer Science, 2013)
In this paper, we extend our previous approach to develop an ID card management system that integrated 2- dimensional Barcode which is responsible to produce secure and reliable identification cards. In our previous [1] work we made use of only photograph of the holder, in order to make it secure from being forged. This time we have extended our approach and it uses photo as well as signature and the identity documents of the holder of the ID card. In this extended approach the system will capture more information including photo and signature and will dynamically generate an image of 2D barcode containing the information provided and will affix this barcode image an ID card. This card will be used to validate and authenticate the holder. Main advantage of using 2D Barcode is its data encoding capacity, 2D Barcode is able to encode up to 500 bytes per square inch.